محددات الطلب على مصادر الوقود في العراق للمدة 1970-1995 - د. احمد حسين الهيتي; عمار محمد سلو احمد (PROSPECTIVE RESEARCHES, 2023)
The Energy Demand Studies are considered as one of the vital subjects which have been discussed heavily by researchers in the field of energy. The importance of the Oil and the Energy are not restricted only to the developed countries, but it was extended to the developing countries too, on this basis we select our research to study the" Energy Demands Determinants in Iraq for the period1970-1995". The research divided to the different:The Demand Theory, The Demand for Energy, The Estimating and Analyzing The Demand Functions For Energy in Iraq, The Future Prediction for the Total Demand on Energy in Iraq, and Results and suggestions. The most important result in this research was The Future Prediction for the Total Demand on Energy in Iraq arrived to (%7.7) as annual growth rate.